Analysis of Elementary School Students' Misconceptions in Science Concepts and Their Remediation Strategies: A Literature Review (2015-2024) - Amrullah, Lalu Azikri; Nasywa Dwi Kamila; Nada Clairina Sophian; Nabila Fitriya; Nurmayanti, Nurmayanti; Bakti, Surya (Indonesian Publication Center, 2025)
Misconceptions at the elementary school level represent a serious cognitive barrier in establishing students' scientific foundations. This article aims to map the science concept areas most prone to misconceptions and analyze the effectiveness of remediation strategies based on scientific publications from 2015–2024. The method employed is a Systematic Literature Review (SLR) of 10 core articles screened using the Publish or Perish application. The analysis reveals that misconceptions predominantly occur in abstract topics such as force and motion, electrical circuits, and photosynthesis. The primary causes include students' intuitive preconceptions, conventional teaching methods, and ambiguous textbook illustrations. These findings confirm that remediation strategies based on the Conceptual Change Model (CCM) and Predict-Observe-Explain (POE), integrated with immersive technologies (AR, virtual simulations, and gamification), are proven most effective in correcting students' cognitive structures. The implications of this study emphasize the importance of routinely using diagnostic instruments to detect misconceptions at an early stage.